2012
DOI: 10.1371/journal.ppat.1002486
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 8 (HHV8) Sequentially Shapes the NK Cell Repertoire during the Course of Asymptomatic Infection and Kaposi Sarcoma

Abstract: The contribution of innate immunity to immunosurveillance of the oncogenic Human Herpes Virus 8 (HHV8) has not been studied in depth. We investigated NK cell phenotype and function in 70 HHV8-infected subjects, either asymptomatic carriers or having developed Kaposi's sarcoma (KS). Our results revealed substantial alterations of the NK cell receptor repertoire in healthy HHV8 carriers, with reduced expression of NKp30, NKp46 and CD161 receptors. In addition, down-modulation of the activating NKG2D receptor, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 77 publications
2
57
0
Order By: Relevance
“…Infection with many viruses induces the surface expression of NKG2DLs (21)(22)(23)(24)(25)(26). Therefore, NKG2D surveillance is a frequent target of viral immune evasion strategies, with many viruses targeting the cell surface display of NKG2DLs.…”
mentioning
confidence: 99%
“…Infection with many viruses induces the surface expression of NKG2DLs (21)(22)(23)(24)(25)(26). Therefore, NKG2D surveillance is a frequent target of viral immune evasion strategies, with many viruses targeting the cell surface display of NKG2DLs.…”
mentioning
confidence: 99%
“…Furthermore, AIDS-KS patients with ongoing symptoms have reduced NK cell-mediated immunity compared to patients with indolent classic KS or normal blood donors [5]. In addition, analysis of 115 patient blood samples showed that NK cells from patients with active KS have reduced cytolytic capacity and NKG2D surface expression, defects that were not seen in normal blood donors or patients with resolved KS [6]. Active KS is also associated with higher serum levels of cytokines and other secreted factors, in particular prostaglandin E2 (PGE2), a pleiotropic hormone that dampens NK cell cytotoxicity, in part by the downregulation of NKG2D expression [6].…”
Section: Innate Immune Recognition Of Kshvmentioning
confidence: 99%
“…In addition, analysis of 115 patient blood samples showed that NK cells from patients with active KS have reduced cytolytic capacity and NKG2D surface expression, defects that were not seen in normal blood donors or patients with resolved KS [6]. Active KS is also associated with higher serum levels of cytokines and other secreted factors, in particular prostaglandin E2 (PGE2), a pleiotropic hormone that dampens NK cell cytotoxicity, in part by the downregulation of NKG2D expression [6]. KSHV infection induces expression of the Cyclooxygenase-2 (COX-2) and production of its metabolite PGE2 [93, 94].…”
Section: Innate Immune Recognition Of Kshvmentioning
confidence: 99%
“…The histologic hallmark of KS is spindle-shaped cells of endothelial origin with slit-like blood vessels and peripheral inflammatory cells. Lesions are classified as patch (earliest foci of KS lesions), plaque (more indurated, edematous, and violaceous), or nodal (visible mass dominated by spindle cells) stages [34,99].…”
Section: Diagnosismentioning
confidence: 99%
“…Use of paclitaxel, a mitotic inhibitor, has been successful in advanced forms of iatrogenic KS [78,114]. Prostaglandin E 2 inhibitors are being investigated [99], as are new interventions targeting paracrine and autocrine cytokines involved in transformation of infected cells [115]. Antioxidants and anti-inflammatory drugs are also being explored as preventive or therapeutic options [42].…”
Section: Iatrogenic/transplant Ksmentioning
confidence: 99%